HUBUNGAN PENGETAHUAN DAN PEKERJAAN IBU DENGAN KELENGKAPAN IMUNISASI PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS KRUI KABUPATEN PESISIR BARAT TAHUN 2023 - Rahmat Agung; Samino Samino; Christin Angelina Febriani Febriani; Agung Aji Perdana (Postgraduate, University of Mataram, 2023)
Immunization is very important for a person's body to be immune from disease. The benefit of immunization is to provide immunity to babies in order to prevent disease and infant death. The immunization achievement based on data from the West Pesisir District Health Service is 2203 (75.7%) in 2022. Meanwhile, based on data from the Krui Health Center, West Pesisir Regency, the immunization achievement of Complete Immunization in 2022 is 266 (75.1%). There are still mothers who do not bring their toddlers for immunization due to several factors including knowledge and work. The aim of this research is to determine the relationship between maternal knowledge and work and the completeness of immunizations for toddlers in the UPTD Work Area of the Krui Health Center, Pesisir Barat Regency in 2023. The research method used by researchers in this study is a correlation study using a cross sectional approach. The number of samples in this study was 175 respondents. The sampling technique used was total sampling. The instrument used was a questionnaire sheet. The statistical test used is the chi-square test. The results of the analysis using the Chi-square test showed a p-value = 0.001 (<0.05) for knowledge and 0.112 for work. The conclusion is that there is a relationship between knowledge and completeness of immunization in the Krui Health Center Work Area in 2023 and there is no relationship between employment and completeness of immunization in the Krui Health Center Work Area in 2023.